1998
DOI: 10.1021/ja9805369
|View full text |Cite
|
Sign up to set email alerts
|

Selective Entry to the Dimeric or Oligomeric Pyridinium Sponge Macrocycles via Aminopentadienal Derivatives. Possible Biogenetic Relevance with Manzamine Alkaloids

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
75
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 22 publications
0
75
0
2
Order By: Relevance
“…Previous studies [8,12,15] managed to synthesise only oligo-alkylpyridinium salts, but biological screening of some of them indicated that the pore-forming capability was abolished [19]. This highlighted the importance of high degree of polymerisation for this kind of biological activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies [8,12,15] managed to synthesise only oligo-alkylpyridinium salts, but biological screening of some of them indicated that the pore-forming capability was abolished [19]. This highlighted the importance of high degree of polymerisation for this kind of biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, refluxing a monomer bearing a terminal chlorine and a linking ether bridge in the alkyl chain, in acetonitrile in the presence of KI for a sustained period, resulted in the production of a mixture of cyclic and linear oligomers with a maximum of 15 monomer units [12]. A rather more sophisticated approach is the formation and subsequent reaction of an N-(2,4-dinitrobenzene) pyridinium salt (Zincke salt) to yield poly-alkylpyridinium salts with up to eight monomer units [15]. The degree of polymerisation can be increased stepwise by the controlled and iterative process of oligomerisation, providing general and practical access to a wide range of linear poly-cationic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…10 They believe that intermediates that are more flexible than bis-dihydropyridine macrocycle (1.9) are the biogenetic precursors to manzamine and related alkaloids. Their hypothesis suggests 5-amino-2,4-pentadienal derivatives lead to the production of pyridinium salts (c.f.…”
Section: Marazano's Modification Of Baldwin's Proposalmentioning
confidence: 99%
“…23 followed by reduction and cyclization of the imine functionality to produce enamine 1.24 (Scheme 5). 10 Scheme 5. Marazano's Modification of Baldwin's Approach.…”
Section: Marazano's Modification Of Baldwin's Proposalmentioning
confidence: 99%
See 1 more Smart Citation